2015
DOI: 10.1590/1519-6984.08113
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of salad greens (Lactuca sativa L. and Eruca sativa Mill.) exposed to crude extracts of toxic and non-toxic cyanobacteria

Abstract: We evaluated the effect of crude extracts of the microcystin-producing (MC+) cyanobacteria Microcystis aeruginosa on seed germination and initial development of lettuce and arugula, at concentrations between 0.5 μg.L -1 and 100 μg.L -1 of MC-LR equivalent, and compared it to crude extracts of the same species without the toxin (MC-). Crude extracts of the cyanobacteria with MC (+) and without MC (-) caused different effects on seed germination and initial development of the salad green seedlings, lettuce being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…Cyanotoxins exhibited phytoinhibitory effects on tested species, depending on the plant species, concentration and kind of toxin. There are a significant number of papers dealing with the effects of cyanotoxin in plants, including alterations of seed germination, development, anatomy, cell arrangement and physiological/biochemical process (Pflugmacher et al, 2006;Lahrouni et al, 2012;Máthé et al, 2013;Azevedo et al, 2014;Bittencourt-Oliveira et al, 2015;Machado et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cyanotoxins exhibited phytoinhibitory effects on tested species, depending on the plant species, concentration and kind of toxin. There are a significant number of papers dealing with the effects of cyanotoxin in plants, including alterations of seed germination, development, anatomy, cell arrangement and physiological/biochemical process (Pflugmacher et al, 2006;Lahrouni et al, 2012;Máthé et al, 2013;Azevedo et al, 2014;Bittencourt-Oliveira et al, 2015;Machado et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The exposition to cyanotoxin disposed deleterious effects on coriander and lettuce germination, growth and DNA. Furthermore, plants can accumulate cyanotoxin (Bittencourt-Oliveira et al, 2015;Nery et al, 2020), so use of water from sources containing cyanobacterial blooms and toxins in plants can induce a food chain contamination with considerable health risk and potential economic losses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some terrestrial plants are sensitive to cyanotoxins as irrigation with water contaminated with cyanotoxins. Previous studies have shown that crude extracts of the cyanobacteria with MC and without MC caused different effects on seed germination and initial development of the salad green seedlings, and lettuce being more sensitive to both extracts when compared to arugula [9]. In addition Dao et al (2014) [10] shown that the germination and seeding growth of some vegetables were damaged under exposure to microcystins contaminated water from the Dau Tieng reservoir.…”
Section: Introductionmentioning
confidence: 98%
“…Studies aimed at understanding these functional activities, especially with regard to antioxidants, are justified because of the growing appeal of the importance of food in health and longevity of man (Benites et al, 2015;Bittencourt-Oliveira et al, 2015;Formagio et al, 2015).…”
Section: Introductionmentioning
confidence: 99%